2019
DOI: 10.1007/s11033-019-05121-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities associated with the midgut microbiota of wild Anopheles gambiae complex in Burkina Faso

Abstract: Plasmodium falciparum is transmitted by mosquitoes from the Anopheles gambiae sensu lato (s.l) species complex and is responsible for severe forms of malaria. The composition of the mosquitoes' microbiota plays a role in P. falciparum transmission, so we studied midgut bacterial communities of An. gambiae s.l from Burkina Faso. DNA was extracted from 17 pools of midgut of mosquitoes from the Anopheles gambiae complex from six localities in three climatic areas, including cotton-growing and cotton-free localiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…atroparvus , the vast majority from the phylum Proteobacteria . Most of the bacterial taxa herein reported have been described as part of the microbiota in culicid mosquitoes ( Dada et al, 2014 ; Muturi et al, 2016 ; Rocha-David et al, 2016 ; Hegde et al, 2018 ; Kang et al, 2020 ) including Anopheles from different geographic regions ( Rani et al, 2009 ; Djadid et al, 2011 ; Wang et al, 2011 ; Boissiere et al, 2012 ; Gimonneau et al, 2014 ; Ngo et al, 2015 ; Bogale et al, 2020 ; Galeano-Castañeda et al, 2020 ; Zoure et al, 2020 ; Feng et al, 2021 ; Silva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…atroparvus , the vast majority from the phylum Proteobacteria . Most of the bacterial taxa herein reported have been described as part of the microbiota in culicid mosquitoes ( Dada et al, 2014 ; Muturi et al, 2016 ; Rocha-David et al, 2016 ; Hegde et al, 2018 ; Kang et al, 2020 ) including Anopheles from different geographic regions ( Rani et al, 2009 ; Djadid et al, 2011 ; Wang et al, 2011 ; Boissiere et al, 2012 ; Gimonneau et al, 2014 ; Ngo et al, 2015 ; Bogale et al, 2020 ; Galeano-Castañeda et al, 2020 ; Zoure et al, 2020 ; Feng et al, 2021 ; Silva et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of midgut microbiota has been studied and identified from various species of mosquitoes, primarily Anopheles mosquitoes ( Tainchum et al., 2020 ; Zoure et al., 2020 ). In contrast, studies of Aedes and Culex mosquitoes are limited ( Tiawsirisup et al., 2018 ; Muturi et al., 2020 ; Seabourn et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of the midgut microbiota has been examined in different species of mosquitoes ( Tiawsirisup et al., 2008 , 2018 ; Guegan et al., 2020 ; Zoure et al., 2020 ). Previous studies have evaluated the influence of colonized microbiota on the susceptibility of mosquitoes to virus and parasitic infection ( Pumpuni et al., 1996 ; Dillon and Dillon, 2004 ; Azambuja et al., 2005 ; Gusmao et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…(Manguin et al, 2013). Other studies have reported the majority of adult mosquito midgut microbiota were Gram-negative species in the phylum Proteobacteria (Tandina et al, 2016;Zoure et al, 2020). At least three mosquitospecific bacterial species have been isolated from the midgut of African malaria vectors in the Gambiae Complex, including Thorsellia anophelis, Janibacter anophelis (Kampfer et al, 2006) and Elizabethkingia anophelis (Kampfer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%